Larvicide Activity on Aedes aegypti of Essential Oil Nanoemulsion from the Protium heptaphyllum Resin - Faustino, Cleidjane Gomes (Molecules, 2020)
The aim of this work was to prepare a nanoemulsion containing the essential oil of Protium heptaphyllum resin and to evaluate the larvicidal activity and the residual larvicidal effect against Aedes aegypti. The essential oil was identified by gas chromatography coupled to a mass spectrometer, and the nanoemulsions were prepared using a low-energy method and characterized by photon correlation spectroscopy. The results indicated the major constituents as p-cimene (27.70%) and α-Pinene (22.31%). Nanoemulsions had kinetic stability and a monomodal distribution in a hydrophilic-lipophilic balance of 14 with particle diameters of 115.56 ± 1.68 nn and zeta potential of −29.63 ± 3.46 mV. The nanoemulsion showed larvicidal action with LC(50) = 2.91 µg∙mL(−1) and residual larvicidal effect for 72 h after application to A. aegypti larvae. Consequently, the nanobiotechnological product derived from the essential oil of P. heptaphyllum resin could be used against infectious disease vectors.